Fueling the mediating role of work ethics in the relationship between intrinsic motivation and work performance - Yunita, Tyna (Enrichment : Journal of Management, 2025)
Many manufacturing workers spend most of their time in workshops, and the work environment significantly impacts factory employees & productivity. Prior research on performance has predominantly focused on occupational roles, and little is known about the antecedent in this field. This study examines the connection between intrinsic motivation, work ethics, and performance. The respondents to this study were manufacturing employees. It is important to research the manufacturing sector because it is a major cause of environmental damage. This is shown by the sector's increasing environmental impact, which is attracting international attention. The manufacturing industry is characterized by a high level of occupational risk. To determine whether intrinsic motivation directly affects work performance. The manufacturing sector has been a pivotal contributor to the growth and prosperity of developing countries, including Indonesia. A total of 120 questionnaires were collected from 178 participants in West Java, Indonesia. SMART PLS was used for measurement and structural equation modeling, with data investigated using SEM. The results of this study indicate that intrinsic motivation only influences work performance when mediated by work ethics. Aside from this, the relationship between intrinsic motivation and work ethics demonstrates a direct influence, and work ethics directly influence work performance. It is noteworthy that intrinsic motivation has no discernible impact on the performance of manufacturing sector workers. The findings offer firms seeking to enhance employee performance and advance sustainable human resources practices in the manufacturing sector a set of actionable insights